History of Protest Literature in India: Trails from the Bhakti Literature - Preeti Oza (International Journal of Interreligious and Intercultural Studies, 2020)
Abstract: â€œBetter is to live one day virtuous and meditative than to live a hundred years immoral and uncontrolledâ€ (The Buddha) Bhakti movement in India has been a path-breaking phenomenon that provided a solid shape and an identifiable face to the abstractions with the help of vernacular language. As a religious movement, it emphasized a strong personal and emotional bond between devotees and a personal God. It has come from the Sanskrit word Bhaj- â€˜to shareâ€™. It began as a tradition of devotional songs, hagiographical or philosophical â€“ religious texts which have generated a common ground for people of all the sects in the society to come together. As counterculture, it embraced into its fold all sections of people breaking the barriers of caste, class, community, and gender. It added an inclusive dimension to the hitherto privileged, exclusivist, Upanishadic tradition. It has provided a very critical outlook on contemporary Brahminical orthodoxy and played a crucial role in the emergence of modern poetry in India. This paper elaborates on the positioning of the Bhakti Movement in the context of Protest narratives in India.